2012
DOI: 10.1080/03075079.2010.549221
|View full text |Cite
|
Sign up to set email alerts
|

University performance evaluations: what are we really measuring?

Abstract: Surveying students to garner feedback on teaching and subject quality are common occurrences in many universities globally. Despite the criticisms surrounding whether measures associated with these surveys are indeed valid, university managers continue to utilise them in key decision making. These surveys mirror business practices where measuring customer satisfaction via surveys is common. However, some argue that universities are misdirected in measuring satisfaction as a proxy for teaching quality, possibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 48 publications
4
79
0
3
Order By: Relevance
“…Yet these performance measures can only be applied at the organisational level, whereas individual instructors/teachers are responsible for the quality of education provided in the delivery of the courses they teach. In assessing their teaching quality, student experiences and perceptions also traditionally play an important role (Arnold 2008;Bedggood and Donovan 2012;Lindsay, Breen, and Jenkins 2002).…”
Section: Research and Teaching Quality Relationship Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet these performance measures can only be applied at the organisational level, whereas individual instructors/teachers are responsible for the quality of education provided in the delivery of the courses they teach. In assessing their teaching quality, student experiences and perceptions also traditionally play an important role (Arnold 2008;Bedggood and Donovan 2012;Lindsay, Breen, and Jenkins 2002).…”
Section: Research and Teaching Quality Relationship Hypothesesmentioning
confidence: 99%
“…Teaching quality/effectiveness is usually gauged via student assessments (Hattie and Marsh 1996). Although the use of student assessments is controversial (Balam and Shannon 2010;Bedggood and Donovan 2012), much of the literature in the area concludes that student assessments are generally consistent and valid (Arnold 2008;Liu 2012).…”
Section: Research and Teaching Quality Relationship Hypothesesmentioning
confidence: 99%
“…Student satisfaction is generally agreed to be the extent to which students are enjoying their studies (Bedggood & Donovan, 2012). Student satisfaction is used 117 as a proxy for good teaching (Bedggood & Donovan, 2012), to rank universities on league tables, and by prospective students in their decision making (Douglas, Douglas, McClelland, & Davies, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most important of these is the quality of instruction, which includes the lecturer personality, perceived knowledge and skill and friendliness and approachability. This factor can account for 50-80 per cent of the variance in student satisfaction ratings (Bedggood & Donovan, 2012). It has become increasingly more important for Australian universities to seek higher satisfaction scores from their students for their educational programs.…”
Section: The Situation In Property Higher Education In Australiamentioning
confidence: 99%
“…Studies within the property discipline within higher education (Newell, 2013;Boyd, 2010;Bedggood & Donovan, 2012) found that at the specific property education level there were key factors influencing the student satisfaction ratings. These included the quality of instruction, the perceived relevance of the instruction and the difficulty of the task.…”
Section: The Situation In Property Higher Education In Australiamentioning
confidence: 99%